Toward reliable morphology assessment of thermosets via physical etching: Vinyl ester resin as an example - J. Karger-Kocsis; A. Wolynski; B. Wetzel; J. Elsäßer; A. Bonyar; S. Grishchuk (eXPRESS Polymer Letters, 2013)
The morphology of peroxide-cured, styrene crosslinked, bisphenol A-based vinyl ester (VE) resin was investigated by atomic force microscopy (AFM) after ‘physical’ etching with different methods. Etching was achieved by laser ablation, atmospheric plasma treatment and argon ion bombardment. Parameters of the etching were varied to get AFM scans of high topography resolution. VE exhibited a nanoscaled nodular structure the formation of which was ascribed to complex intra- and intermolecular reactions during crosslinking. The microstructure resolved after all the above physical etching techniques was similar provided that optimized etching and suitable AFM scanning conditions were selected. Nevertheless, with respect to the ‘morphology visualization’ these methods follow the power ranking: argon bombardment > plasma treatment > laser ablation.